Phytosociological Studies on Natural Populations of Terminalia chebula Retz. in District Hamirpur, Himachal Pradesh - Singh, Samanpreet; Sharma, Kamal; Sharma, Dushyant (International Journal of Economic Plants, 2020)
The present phytosociological study was conducted on five natural populations of Terminalia chebula Retz. Distributed in Hamirpur district of with the objective to study vegetation structure and distribution pattern of different tree and shrub species in these populations. In each natural population five quadrats of 20 x 20 m (400 m2) size were randomly laid to examine tree species and for the analysis of shrubs, a sub-square of 5x 5 m (25 m2) size was chosen in each quadrat. Terminalia chebula Retz. was found dominant among tree species in all populations, while among shrubs Murraya koengii was dominant species. Species richness in trees ranged from 1.13 to 2.69 and in shrubs it ranged from 0.28 to 0.54.